Analisis Swot dalam Menentukan Strategi Pemasaran pada Toko Nadhifa Cake Karawang - Sri Intan Nuraeni; Enjang Suherman; Laras Ratu Khalida (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Nadhifa Cake cake shop is one of the cake shops operating in Karawang. This research aims to determine and analyze the marketing strategies used by the Nadhifa Cake cake shop, as well as to determine the position of the Nadhifa Cake cake shop using SWOT analysis. The first analysis was carried out through IFAS and EFAS analysis contained in Nadhifa Cake. Next, use the SWOT matrix to analyze Nadhifa Cake's strengths, weaknesses, opportunities and threats. The results of this analysis are used to determine the position of the Nadhifa Cake quadrant.The method used in this research is descriptive qualitative to analyze internal and external factors using the SWOT matrix. Data was obtained from interviews with the owner and a survey of 6 consumers using Google Form to get an assessment.The research results show that Nadhifa Cake is in quadrant II. This means that Nadhifa Cake has sufficient internal strength to face external threats. The right strategy for Nadhifa Cake is a diversification strategy, namely utilizing its internal strengths to develop products that can meet the needs and desires of a wider range of customers.